Meninjau Kembali Bukti Kenabian Mirza Ghulam Ahmad: Sebuah Studi Kritis - Askar, Romlah Abubakar (AL QUDS : Jurnal Studi Alquran dan Hadis, 2023)
The concept of prophethood in Ahmadiyah's view has the consequence that there is still the possibility of prophets after Prophet Muhammad SAW. This begins with several hadith narrations about the final prophet. Based on semantic analysis, the meaning of the word 'khÄtam al-ambiya' from the Ahmadiyya perspective is separated from the historical and sociological context when the word is used. Ahmadiyah just stopped interpreting it grammatically, not seeing the historical and sociological side of the word. In the grammatical and historical-sociological meaning, the meaning of the word is closing, which means when it is connected with the word 'al-anbiya' it means the end of the prophets. The existence of the prophet Isa at the time of the apocalypse, does not have the status of a new prophet, but his status as a prophet who was sent before the prophet Muhammad, and he also brought the Shari'a of the Prophet Muhammad SAW. Not to be a new prophet and bring new messages.Â